Eros and Ethos in the political and religious Logos of the "Persiles". The anomic character in Cervantes - Maestro, Jesús G. (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper presents an approach to the novel Los trabajos de Persiles y Sigismunda by Miguel de Cervantes about the conflicts that the dialectic between personal Eroticism and religious Logos supposes for various characters. The cervantine literature does not always confirm the norms imposed by the counter-reformist religion for love relationships, but it even seems to discuss them in an ironic and critical way.
Keywords: Cervantes; Persiles; Eros; Ethos; Logos; anomie